Optimizing the sequencing of tyrosine kinase inhibitors (TKIs) in epidermal growth factor receptor (EGFR) mutation-positive non-small cell lung cancer (NSCLC) - Gelatti, Ana (Lung Cancer, 2019)
Non-small cell lung cancer (NSCLC) is the most common type of lung cancer, accounting for 80–85% of cases. Epidermal growth factor receptor (EGFR) mutations are observed in approximately 40% and 20% of patients with NSCLC in Asian and non-Asian populations, respectively. First-generation (gefitinib, erlotinib) and second-generation (afatinib, dacomitinib) EGFR-tyrosine kinase inhibitors (TKIs) have been standard-of-care (SoC) first-line treatment for patients with sensitizing EGFR mutation positive advanced NSCLC following Phase III trials versus platinum-based doublet chemotherapy. However, most patients treated with first-line first- or second-generation EGFR-TKIs develop resistance. Osimertinib, a third-generation, central nervous system active EGFR-TKI which potently and selectively inhibits both EGFR-TKI sensitizing (EGFRm) and the most common EGFR T790M resistance mutations, has shown superior efficacy versus first-generation EGFR-TKIs (gefitinib / erlotinib). Osimertinib is now a treatment option for patients with advanced NSCLC harboring EGFRm in the first-line setting, and treatment of choice for patients with T790M positive NSCLC following disease progression on first-line EGFR-TKIs. The second-generation EGFR-TKI dacomitinib has also recently been approved for the first-line treatment of EGFRm positive metastatic NSCLC. There remains a need to determine appropriate sequencing of EGFR-TKIs in this setting, including EGFR-TKIs as monotherapy or in combination with other TKIs / signaling pathway inhibitors. This review considers the evolving role of sequencing treatments to maximize benefits for patients with EGFRm positive advanced NSCLC.